The Effectiveness of Tri Hita Karana Based Traditional Village Management in Covid-19 Prevention at Bali - Sari, Ni Putu Mirna; Sukadi, Bimo Dwi Nur Romadhon; Yasintha, Putu Nomy (Faculty of Social and Political Science Universitas Brawijaya, 2021)
Traditional villages are original autonomous villages that control the self-government whells within the palemahan (territories) that are still alive. Their position is recognized in the government system of the Unitary State of Indonesian Republic. The Covid-19 pandemic that is currently happening is causing an economic slowdown and a decline in public health. The Regional Government of Bali Province issued a policy in Bali Governor Regulation Number 15 of 2020 regarding the Policy for the Acceleration of Handling Covid-19 in the Province of Bali by reallocating a Traditional Village Fund of Rp. 300,000,000.00 for the response to Covid-19 by involving the soldiers and manners of the Traditional Village. The effectiveness of the management of the Traditional Village Fund is based on local wisdom, where the principles of Tri Hita Karana (Parahyangan, Pawongan, and Palemahan) as a philosophical foundation that are held in carrying out every activity, program, and policy are the focus of this research. The implementation of Tri Hita Karana provides a new color in financial management in Indonesia. Technical implementation, reporting, prosecution of alleged fraud, and accountability in a consultative manner and rich in local wisdom values upheld by Bendesa, Prajuru Desa Adat, and Krama Desa positively impact influencing the mindset and behavior of the community in complying with existing regulations or policies set. However, it cannot be denied that there are still contradictions between the governance of traditional villages in Bali and the ideal sound governance principles in implementing village governance, especially in terms of transparency and accountability.